Distribution of bats in the subtropical regions of the Black Sea coast and adjacent territories - A. N. Ivanitzky; A. Yu. Alekseev (Юг России: экология, развитие, 2024)
Aim. The Black Sea region is one of the centers of diversity of bats in the Palearctic. In this regard, the main aim of the work was determined ‐ to study the species composition of the bat fauna of the Black Sea region and the distribution of bat species there. The aim becomes especially relevant if we consider that significant changes have occurred in the composition of the region’s fauna in recent years and that the distribution of chiropterans in the Black Sea region as a whole has never been the object of special research.   Discussion. The article contains point maps of the distribution of each of the 35 species of bats living in the subtropics of the Black Sea region and adjacent territories. In addition, the maps are provided with comments on the range of each species on the Black Sea coast.   Conclusion. The data presented can be used both for fundamental research and for solving practical problems, primarily in the organization and implementation of environmental measures.